2018
DOI: 10.1002/fld.4482
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of numerical modeling in the solution of incompressible viscous flow problems using finite element method based on spherical Hankel shape functions

Abstract: Summary In this paper, the finite element method with new spherical Hankel shape functions is developed for simulating 2‐dimensional incompressible viscous fluid problems. In order to approximate the hydrodynamic variables, the finite element method based on new shape functions is reformulated. The governing equations are the Navier‐Stokes equations solved by the finite element method with the classic Lagrange and spherical Hankel shape functions. The new shape functions are derived using the first and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…According to the literature, shape parameters are constants used in RBFs to increase the accuracy [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. It can be said that any specific problem requires the most suitable shape parameter by its own nature provided that high accuracy is demanded.…”
Section: Buckling Of Rectangular Platementioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, shape parameters are constants used in RBFs to increase the accuracy [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. It can be said that any specific problem requires the most suitable shape parameter by its own nature provided that high accuracy is demanded.…”
Section: Buckling Of Rectangular Platementioning
confidence: 99%
“…By way of illustration, conical, multiquadric, inverse multiquadric, Gaussian, and J-Bessel [12] has just one shape parameter, whilst complex Fourier [11] and Hankel RBFs [21][22][23] have two of them. For the Hankel shape functions, n and e are the shape parameters that belong to the set of whole numbers and positive real numbers, respectively.…”
Section: Buckling Of Rectangular Platementioning
confidence: 99%
See 1 more Smart Citation
“…The spherical Hankel radial basis function (RBF) with all of its advantageous features plays the main role here. Recently, the implementations of these functions in solving elastostatic and elastodynamic problems using boundary element method and incompressible viscous flow problems using FEM were presented by Hamzehei Javaran et al There are two kinds of RBFs reported in the literature, including oscillatory and nonoscillatory ones. The conical functions, thin plate splines, Gaussian functions, multiquadric, inverse multiquadric, and compact supported functions can be mentioned as nonoscillatory RBF, while real and complex Fourier RBF and J‐Bessel RBF belong to the oscillatory class.…”
Section: Introductionmentioning
confidence: 99%